Women & Girls on the Autism Spectrum: A Profile - B. Lawson, Wenn (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Being female and autistic is poorly understood, but is autism really ‘rare’ in females? Historically, autism has been associated with traditionally masculine features and stereotypes of behaviour, with some believing autism only occurred in males [1]. This leads scientific enquiry to the critical question of whether there are more males living with autism or, conversely, do females on the autistic spectrum present differently to males and, therefore, are at risk of remaining undiagnosed?